Performance optimization design method of trans-perovskite solid electrolyte

By constructing and optimizing the crystal lattice and electronic structure of two-dimensional layered hydrogen perovskite, the problem of low ionic conductivity of solid electrolyte materials in lithium metal batteries is solved, and higher ionic conductivity and Stability, meets applications with higher battery performance requirements.

CN119418833APending Publication Date: 2025-02-11CHONGQING UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411543513.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The liquid/gel electrolytes in existing lithium metal batteries have defects such as flammable and corrosion-free, and the solid electrolyte materials have low ionic conductivity, which cannot meet the application scenarios where battery performance requirements are higher.

Method used

By constructing two-dimensional layered hydrogen oxygen element trans perovskites with different hydrogen oxygen element distributions, the lattice structure and electronic structure are optimized to improve the ionic conductivity and stability of the material. Specific steps include building a two-dimensional layered structure, optimizing lattice parameters, calculating phonon structure and decomposition energy, simulating defects and diffusion types, and calculating ionic conductivity.

Benefits of technology

It improves the ionic conductivity and stability of trans perovskite solid electrolytes, provides more efficient ion conduction paths and more stable electronic structures, and meets the application scenarios with higher performance requirements of lithium metal batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119418833A_ABST
    Figure CN119418833A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, and discloses a trans-perovskite solid electrolyte performance optimization design method, which comprises the following steps: S1, constructing two-dimensional layered double-oxygen-group element trans-perovskite with different double-oxygen-group element distributions, optimizing crystal lattices and obtaining ground state energy, lattice parameters of the two-dimensional layered double oxygen group element trans-perovskite are determined; s2, analyzing the stability of the two-dimensional layered double-oxygen-group element trans-perovskite by calculating a phonon structure and decomposition energy; s3, constructing a two-dimensional layered double-oxygen-group element trans-perovskite supercell model, simulating different defect types and different diffusion types, and analyzing a diffusion mechanism of ions in the two-dimensional layered double-oxygen-group element trans-perovskite; and S4, calculating the ionic conductivity of the two-dimensional layered dioxygen group element trans-perovskite. According to the technical scheme, the structure of the trans-perovskite material is optimized, so that the ionic conductivity and the stability of the solid electrolyte are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-ion batteries, and in particular to a performance optimization design method for an inverse perovskite solid electrolyte. Background Art

[0002] Lithium-ion batteries are widely used in many fields. However, with the rapid development of electronic products and electric vehicles, people's requirements for battery performance are increasing. Current lithium-ion batteries are mainly based on graphite negative electrodes, but their theoretical capacity is relatively low. Replacing graphite with lithium metal with higher capacity and developing lithium metal batteries is an effective way to increase battery capacity.

[0003] The liquid / gel electrolytes in current lithium metal batteries have defects such as flammability and corrosion. During the battery charging and discharging process, the metal negative electrode will form dendrites at the interface, which can easily pierce the diaphragm of the liquid electrolyte, causing a short circuit inside the battery and causing many safety problems. Compared with traditional liquid electrolytes, solid electrolytes have significant advantages in electrochemical stability and mechanical strength, and are expected to fundamentally eliminate the safety hazards of all-solid-state lithium metal batteries.

[0004] Existing solid electrolyte materials generally include inorganic ceramics, polymers and composite materials. Among them, inorganic ceramic materials have excellent mechanical strength and can effectively inhibit the growth of dendrites at the interface, making them an ideal solid electrolyte material. The earlier discovered ceramic solid electrolytes include LiPON and Li 3 N, LiPON has high mechanical strength, but low ionic conductivity (10 -8 -10 -6 S cm -1 ). 3 N has good ionic conductivity (10 -3 S cm -1 ), but its electrochemical window is only 0.445V, which limits its practical application in batteries. NASICON solid electrolyte material AM 2 (PO 4 ) 3 , generally have high ionic conductivity, but they are often unstable when in contact with lithium metal anode. 5 La 3 M 2 O 12 , has good Li ion conductivity (10 -4 S cm -1 ), but there is a large interface impedance between it and the electrode.

[0005] In recent years, perovskite materials have shown excellent performance in many fields (such as solid oxide fuel cells, solar cells, etc.). The chemical formula of perovskite is usually ABX 3 ,like Figure 1 As shown, the B-site cation and the X-site anion together form an octahedron with connected vertices, while the A-site cation fills the gap between the octahedrons. Figure 1 It can be seen that the content of ions at the corners of the octahedron is significantly higher than that of other ions. Therefore, it can be seen that the ionic conductivity in perovskite mainly comes from the diffusion of ions at the corners of the octahedron. 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-δ ) often have high oxygen ion conductivity and can be used as electrode materials for solid oxide fuel cells. Among Li ion solid electrolyte materials, there is a class of oxide perovskite materials Li 0.5 La 0.5 TiO 3 (LLTO). At room temperature, the Li ion conductivity of LLTO is 2×10 -5 S cm -1 , which is much lower than the 10 required by solid-state batteries. -3 S cm -1 This is because the Li ions can only fill the gaps in the octahedron, and their content is relatively small, resulting in lower ionic conductivity. Based on this, Zhao Yusheng and others designed and proposed a lithium-rich inverse perovskite, whose common chemical formula is A 3 This type of inverse perovskite is also composed of octahedrons connected at the vertex, but the difference is that the positions of anions and cations are opposite to those of formal perovskites, such as Figure 2 As shown in Figure 1, in the inverse perovskite, Li ions occupy the octahedral vertices and their content is relatively high. Therefore, the Li ion conductivity is greatly improved compared to the oxide perovskite LLTO. 3 OCl has a 0.85×10 - 3 S cm -1 The ionic conductivity is much higher than that of LLTO (2×10 -5 S cm -1 However, in the three-dimensional structure of Li 3 In OCl, Li ions are mainly transported through vacancy transition mechanism. Because of this, the transport of Li ions is restricted by the concentration of vacancy defects. 3In OCl, the vacancy defect concentration is at a relatively low level, resulting in relatively low ionic conductivity, which cannot meet application scenarios with higher requirements for battery performance, so the performance of the material needs to be further optimized. Summary of the invention

[0006] The present invention aims to provide a performance optimization design method for a trans-perovskite solid electrolyte, which improves the ionic conductivity and stability of the solid electrolyte by optimizing the structure of the trans-perovskite material.

[0007] To achieve the above object, the present invention adopts the following technical solution: a performance optimization design method of an inverse perovskite solid electrolyte, comprising the following steps:

[0008] S1: Construct two-dimensional layered dioxygen trans perovskites with different dioxygen distributions, optimize the lattice and obtain the ground state energy, and determine the lattice parameters of the two-dimensional layered dioxygen trans perovskites;

[0009] S2: Analyze the stability of two-dimensional layered dioxo-element trans-perovskites by calculating phonon structure and decomposition energy;

[0010] S3: Construct a two-dimensional layered dioxygen trans-perovskite supercell model, simulate different defect types and different diffusion types, and analyze the diffusion mechanism of ions in the two-dimensional layered dioxygen trans-perovskite;

[0011] S4: Calculate the ionic conductivity of two-dimensional layered dioxo-element trans-perovskites.

[0012] Preferably, in S1, the chemical formula of the two-dimensional layered dioxygen element trans-perovskite is: Li 2 M 2 OCh 2 , where M is Mg 2+ , Mn 2+ , Fe 2+ 、Co 2+ 、Ni 2+ 、Zn 2+ Ch is any one of S, Se, and Te.

[0013] Preferably, in S1, the process of constructing a two-dimensional layered dioxygen element trans perovskite with different dioxygen element distributions is as follows: first, select an M 2+ Metal cations can construct two-dimensional layered structures with different distributions of dioxo elements by changing the type of oxo elements Ch.

[0014] Preferably, in S1, the lattice of the two-dimensional layered structure with different dioxygen elements is optimized by ab initio molecular dynamics method. The specific operation process is: when constructing the lattice, Li and M2+ A random distribution is performed, and then the energy of the various lattice structures constructed is calculated. Following the principle that the lower the energy, the more stable the structure, the structure with relatively low energy is judged as the better structural choice, and the corresponding lattice parameters are used as the required parameters.

[0015] Preferably, in S2, density functional perturbation theory (DFPT) is used to calculate the phonon structure of two-dimensional layered dioxygen element trans-perovskite with different dioxygen element distributions, and the stability of the material is judged based on whether there is an imaginary frequency in the phonon spectrum.

[0016] Preferably, in S2, the decomposition energy of the two-dimensional layered dioxygen element trans-perovskite is calculated as follows:

[0017]

[0018] The stability of the material is judged by the positive or negative value of ΔE.

[0019] Preferably, in S3, a two-dimensional layered dioxygen element trans-perovskite supercell model is constructed using VESTA software, and the supercell energy without defects, the supercell energy with defects, and the energy of the defect material itself are calculated respectively, and the defect formation energy is calculated according to the following formula:

[0020] E form =E defect -E perfect +E defect-species

[0021] Among them, E form is the defect formation energy, E defect is the supercell energy including defects, E perfect is the supercell energy without defects, E defect-species The energy of the defect material itself is used to determine the ion diffusion performance by the defect formation energy and the transition energy barrier.

[0022] Preferably, in S3, the simulated defect types include vacancy defects, interstitial defects and vacancy-interstitial defect pairs.

[0023] Preferably, in S3, the simulated diffusion types include vacancy transitions and interstitial ion transitions.

[0024] Preferably, in S4, the ionic conductivity σ is calculated using the Arrhenius equation:

[0025]

[0026] Among them, σ 0 is the pre-exponential factor, T is the Kelvin temperature, k Bis the Boltzmann constant, Ea is the activation energy of ion transition, and e is a natural constant.

[0027] Compared with the prior art, the beneficial technical effects of this technical solution are:

[0028] (1) After in-depth research, the inventors found that in the three-dimensional trans-perovskite, the diffusion of Li ions mainly follows the vacancy transition mechanism. However, in the two-dimensional trans-perovskite, the situation is different. Li ions can not only diffuse through vacancy transitions, but also diffuse through interlayer gaps. Specifically, the lattice gaps of the octahedron provide additional channels for the diffusion of ions. This unique structure allows ions to have more diffusion path options in the two-dimensional trans-perovskite, thereby effectively improving the ionic conductivity of the material; this discovery is of great significance for a deep understanding of the relationship between the structure and performance of trans-perovskites, and also provides new ideas and directions for further optimizing material performance to meet higher application scenarios.

[0029] (2) The inventors also found in the process of in-depth research that for two-dimensional inverse perovskite (whose chemical formula is Li 4 BX 2 , where B is any one of O, S, Se, Te; X is any one of Cl, Br, I), when two Li ions are separated by two M 2+ When the metal cations are substituted, based on the principle of lattice electrical neutrality, the -1 valence halogen ions in the octahedral interstitial will be replaced by -2 valence oxygen ions, thereby forming a two-dimensional layered dioxygen element trans perovskite Li in which both the center and the interstitial of the octahedron are occupied by -2 valence oxygen elements. 2 M 2 OCh 2 , this doping M 2+ The manipulation of metal cations will have a significant impact on the electronic structure of two-dimensional inverse perovskites. Specifically, it can change the distribution and interaction of electrons inside the material, causing changes in the transmission path and energy state of electrons in the lattice, ultimately achieving the effect of improving the ionic conductivity of the material. This discovery provides new ideas and methods for optimizing the performance of two-dimensional inverse perovskite materials, which is of great significance for promoting the development of lithium metal batteries.

[0030] (3) This technical solution combines the two-dimensional structure with M 2+ The synergistic effect of the dioxygen structure formed by metal cation doping further improves the ionic conductivity of the material. The two-dimensional structure provides more diverse ion diffusion paths, and M 2+The special dioxygen structure formed by metal cation doping optimizes the ion transmission environment from the electronic structure level. The two work together to promote the conduction efficiency of ions in the material, making the material perform better in ion conductivity.

[0031] (4) This technical solution uses theoretical simulation methods to construct two-dimensional layered dioxygen element trans-perovskite structures with different dioxygen element distributions, and conducts in-depth research and analysis on them. In this way, materials with relatively excellent stability and ionic conductivity can be screened out, and rich data are accumulated for the performance optimization of trans-perovskite solid electrolytes, and solid theoretical support is provided, which is of great significance for the research of all-solid-state batteries and helps promote the development and application of all-solid-state battery technology.

[0032] (5) Using theoretical simulation methods, we have successfully established a connection between microscopic atomic arrangements and macroscopic properties. This connection enables researchers to simulate and predict various properties of materials on computers without having to conduct a large number of tedious experimental attempts, thereby greatly accelerating the development of materials. At the same time, it reduces the manpower, material resources and time costs required in the experimental process, effectively reduces the cost of material development, improves development efficiency, and brings many conveniences and advantages to material science research and practical applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The perovskite ABX 3 structure;

[0034] Figure 2 The trans-perovskite A in the prior art 3 The structure of BX;

[0035] Figure 3 Li in the present invention 2 M 2 OCh 2 structure. DETAILED DESCRIPTION

[0036] The following is further described in detail through specific implementation methods:

[0037] Example

[0038] A performance optimization design method for an inverse perovskite solid electrolyte comprises the following steps:

[0039] S1: Construct two-dimensional layered dioxygen element trans-perovskite with different dioxygen element distributions, whose chemical formula is: Li 2 M 2 OCh 2 , where M is Mg 2+ , Mn2+ , Fe 2+ 、Co 2+ 、Ni 2+ 、Zn 2+ Any one of; Ch is any one of S, Se, Te, Figure 3 For Li 2 M 2 OCh 2 structure, optimize the lattice and obtain the ground state energy, and determine the lattice parameters of the two-dimensional layered dioxygen element trans-perovskite;

[0040] S1.1: The process of constructing two-dimensional layered dioxygen element trans-perovskites with different dioxygen element distributions is as follows: first select an M 2+ Metal cations, by changing the type of oxygen group element Ch, can construct a two-dimensional layered structure with different distributions of dual oxygen group elements;

[0041] S1.2: The lattice of the two-dimensional layered structure with different dioxygen elements was optimized by ab initio molecular dynamics. The specific operation process is as follows: when constructing the lattice, Li and M 2+ Random distribution is performed, and then the energy of various lattice structures constructed is calculated. Following the principle that the lower the energy, the more stable the structure, the structure with relatively low energy is determined as the better structural choice, and the corresponding lattice parameters are used as the required parameters; by optimizing the lattice of the two-dimensional layered structure with different dioxygen element distributions, reasonable lattice parameters are obtained, and the determined lattice parameters are used for the calculation of the phonon structure in S2 and the construction of the supercell model in S3;

[0042] S2: Analyze the stability of two-dimensional layered dioxo-element trans-perovskites by calculating phonon structure and decomposition energy;

[0043] S2.1: Use density functional perturbation theory (DFPT) to calculate the phonon structure of two-dimensional layered dioxygen element trans-perovskite with different dioxygen element distributions. The stability of the material is judged based on whether there is an imaginary frequency in the phonon spectrum. If there is an imaginary frequency in the phonon spectrum, it means that the material is unstable; if there is no imaginary frequency in the phonon spectrum, it means that the material is relatively stable.

[0044] S2.2: The decomposition energy of two-dimensional layered dioxygen element trans-perovskite is calculated as:

[0045]

[0046] The stability of the material is judged by the positive or negative value of ΔE; if ΔE>0, the decomposition reaction is an exothermic reaction, indicating that the material is unstable; if ΔE<0, the decomposition reaction is an endothermic reaction, indicating that the material is stable;

[0047] S3: Construct a two-dimensional layered dioxygen trans perovskite supercell model, simulate different defect types and different diffusion types, and analyze the diffusion mechanism of ions in the two-dimensional layered dioxygen trans perovskite. The defect types include vacancy defects, interstitial defects, and vacancy-interstitial defect pairs. The simulated diffusion types include vacancy transitions and interstitial ion transitions. Specifically, VESTA software is used to construct a two-dimensional layered dioxygen trans perovskite supercell model, and the supercell energy without defects, the supercell energy with defects, and the energy of the defect material itself are calculated respectively. The defect formation energy is calculated according to the following formula:

[0048] E form =E defect -E perfect +E defect-species

[0049] Among them, E form is the defect formation energy, E defect is the supercell energy including defects, E perfect is the supercell energy without defects, E defect-species The energy of the defect material itself is used to determine the ion diffusion performance. The lower the defect formation energy and transition energy barrier, the better the ion diffusion performance.

[0050] S4: Calculate the ionic conductivity of two-dimensional layered dioxo-element trans-perovskite; the ionic conductivity σ is calculated using the Arrhenius equation:

[0051]

[0052] Among them, σ 0 is the pre-factor ( where N is the number of transition ions (in this study, N = 1), P is the number of nearest neighbor sites (which can be determined based on the specific transition path in the supercell structure), and ν is the lattice oscillation frequency (about 10 12 Hz), d is the transition distance (which can be determined based on the specific transition path in the supercell structure), q is the charge of the transition ion (q = 1 for lithium ions in this study), V is the supercell volume (which can be calculated based on the optimized supercell structure); T is the Kelvin temperature; k B is the Boltzmann constant, which is 1.38×10 -23 J / K; Ea is the activation energy of ion transition, which can be simply approximated as the formation energy of defect E form and transition barrier E barrier The diffusion barrier Ebarrier can be directly obtained by the Climbing Image Nudged Elastic Band (CINEB) method, and the defect formation energy E formIt can be calculated using the previous formula; e is a natural constant, and its value is 2.71828.

[0053] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.

Claims

1. A performance optimization design method for an inverse perovskite solid electrolyte, characterized in that: The following steps are involved: S1: Construct two-dimensional layered dioxygen trans perovskites with different dioxygen distributions, optimize the lattice and obtain the ground state energy, and determine the lattice parameters of the two-dimensional layered dioxygen trans perovskites; S2: Analyze the stability of two-dimensional layered dioxo-element trans-perovskites by calculating phonon structure and decomposition energy; S3: Construct a two-dimensional layered dioxygen trans-perovskite supercell model, simulate different defect types and different diffusion types, and analyze the diffusion mechanism of ions in the two-dimensional layered dioxygen trans-perovskite; S4: Calculate the ionic conductivity of two-dimensional layered dioxo-element trans-perovskites.

2. The performance optimization design method of a trans-perovskite solid electrolyte according to claim 1, characterized in that: In S1, the chemical formula of the two-dimensional layered dioxygen element trans-perovskite is: Li2M2OCh2, where M is Mg 2+ , Mn 2+ , Fe 2 + 、Co 2+ 、Ni 2+ 、Zn 2+ Ch is any one of S, Se, and Te.

3. The performance optimization design method of a trans-perovskite solid electrolyte according to claim 2, characterized in that: In S1, the process of constructing two-dimensional layered dioxygen element trans-perovskites with different dioxygen element distributions is as follows: first, select an M 2+ Metal cations can construct two-dimensional layered structures with different distributions of dioxo elements by changing the type of oxo elements Ch.

4. The performance optimization design method of a trans-perovskite solid electrolyte according to claim 3, characterized in that: In S1, the ab initio molecular dynamics method was used to optimize the lattice of the two-dimensional layered structure with different dioxygen elements. The specific operation process was as follows: when constructing the lattice, Li and M 2+ A random distribution is performed, and then the energy of the various lattice structures constructed is calculated. Following the principle that the lower the energy, the more stable the structure, the structure with relatively low energy is judged as the better structural choice, and the corresponding lattice parameters are used as the required parameters.

5. The performance optimization design method of a trans-perovskite solid electrolyte according to claim 4, characterized in that: In S2, the density functional perturbation theory (DFPT) is used to calculate the phonon structure of two-dimensional layered dioxo-element trans-perovskites with different dioxo-element distributions, and the stability of the material is judged based on whether there is an imaginary frequency in the phonon spectrum.

6. The performance optimization design method of a trans-perovskite solid electrolyte according to claim 5, characterized in that: In S2, the decomposition energy of two-dimensional layered dioxygen element trans-perovskite is calculated as: The stability of the material is judged by the positive or negative value of ΔE.

7. The performance optimization design method of a trans-perovskite solid electrolyte according to claim 6, characterized in that: In S3, VESTA software was used to construct a two-dimensional layered dioxygen element trans-perovskite supercell model, and the supercell energy without defects, the supercell energy with defects, and the energy of the defect material itself were calculated respectively. The defect formation energy was calculated according to the following formula: AND form =And defect -AND perfect +E defect-species Among them, E form is the defect formation energy, E defect is the supercell energy including defects, E perfect is the supercell energy without defects, E defect-species The energy of the defect material itself is used to determine the ion diffusion performance by the defect formation energy and the transition energy barrier.

8. The performance optimization design method of a trans-perovskite solid electrolyte according to claim 7, characterized in that: In S3, the simulated defect types include vacancy defects, interstitial defects, and vacancy-interstitial defect pairs.

9. The performance optimization design method of a trans-perovskite solid electrolyte according to claim 8, characterized in that: In S3, the simulated diffusion types include vacancy transitions and interstitial ion transitions.

10. The performance optimization design method of a trans-perovskite solid electrolyte according to claim 9, characterized in that: In S4, the ionic conductivity σ is calculated using the Arrhenius equation: Where σ0 is the pre-exponential factor, T is the Kelvin temperature, k B is the Boltzmann constant, Ea is the activation energy of ion transition, and e is a natural constant.